Mesenchymal Stem Cells Preserve Working Memory in the 3xTg-AD Mouse Model of Alzheimer's Disease - Ruzicka, Jiri; Kulijewicz-Nawrot, Magdalena; Rodrigez-Arellano, Jose Julio; Jendelova, Pavla; Sykova, Eva (International journal of molecular sciences, 2016)
The transplantation of stem cells may have a therapeutic effect on the pathogenesis and progression of neurodegenerative disorders. In the present study, we transplanted human mesenchymal stem cells (MSCs) into the lateral ventricle of a triple transgenic mouse model of Alzheimer's disease (3xTg-AD) at the age of eight months. We evaluated spatial reference and working memory after MSC treatment and the possible underlying mechanisms, such as the influence of transplanted MSCs on neurogenesis in the subventricular zone (SVZ) and the expression levels of a 56 kDa oligomer of amyloid β (Aβ*56), glutamine synthetase (GS) and glutamate transporters (Glutamate aspartate transporter (GLAST) and Glutamate transporter-1 (GLT-1)) in the entorhinal and prefrontal cortices and the hippocampus. At 14 months of age we observed the preservation of working memory in MSC-treated 3xTg-AD mice, suggesting that such preservation might be due to the protective effect of MSCs on GS levels and the considerable downregulation of Aβ*56 levels in the entorhinal cortex. These changes were observed six months after transplantation, accompanied by clusters of proliferating cells in the SVZ. Since the grafted cells did not survive for the whole experimental period, it is likely that the observed effects could have been transiently more pronounced at earlier time points than at six months after cell application.
Keywords: modely nemocí na zvířatech; glutaminsynthetasa; Cell Proliferation; Alzheimer’s disease; krátkodobá paměť; Maze Learning; Mesenchymal Stem Cell Transplantation; Alzheimerova nemoc; Alzheimer Disease; amyloidní beta-protein; neurogenesis; mesenchymal stem cells; bludiště - učení; Animals; lidé; Neurogenesis; myši transgenní; Amyloid beta-Peptides; Humans; ventriculi laterales; zvířata; Disease Models, Animal; myši; Aβ*56; proliferace buněk; neurogeneze; Mice; transplantace mezenchymálních kmenových buněk; Glutamate-Ammonia Ligase; Memory, Short-Term; working memory; Mice, Transgenic; Lateral Ventricles